MANAJEMEN BERBASIS SEKLAH DI UPTD SPNF SKB KOTA SALATIGA - Muflikah; Noormiyono (STKIP Subang, 2024)
Centralized education does not train school leadership to be more independent and in terms of administration, teacher professionalism, institutional development, development curriculum, provision of teaching aids, allocation of funds and especially increasing community involvement to increase school ownership. Objectives Based on this research, it is determined that school management-based development is important for schools. This research method is a literature review. The research results were obtained by looking for similarities in several articles and then drawing conclusions. The results and impact of implementing SBM on optimal performance, learning, learning resources and professionalism of teachers and school management systems are known. Through SBM, as a result, there is greater community and parent participation, school principals can become more democratic, professional and competent in forming integrated teams in preparing, implementing and evaluating school activity programs. In implementing MBS. The conclusion is to make quality training more effective, so that our nation can also achieve excellence. Conclusion: The results of implementing SBM cannot be achieved in all schools equally. But all schools have the same acceptance of quality schools.